THE INTERACTION OF THE PRESCHOOL EDUCATIONAL ORGANIZATION WITH THE FAMILY AS A FACTOR IN THE SOCIAL DEVELOPMENT OF PRESCHOOL CHILDREN - akramova, matluba (Центр Научных Публикаций (buxdu.uz), 2021)
It is known that childhood is a unique and special period in the life of every person. In childhood, the foundations of a child’s health are laid and his or her personality is also formed: guidelines, preferences, values. A child’s childhood has a direct impact on the success of his or her future life. Social development is a valuable experience in this period. It should be noted that the psychological readiness of a child for school depends in many respects on the situation.